2008
DOI: 10.1002/anie.200801713
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Emission from Bis‐PtII Complexes of Doubly N‐Confused Calix[6]phyrins(1.1.1.1.1.1)

Abstract: Light from confusion: A set of doubly N‐confused calix[6]phyrins bearing two coordination sites (NNNC,NNNC or NNNN,NNCC) were synthesized. Their bis‐PtII complexes exhibit near‐infrared emission around 1000 nm, which could make these compounds ideal for biological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 19 publications
0
39
0
2
Order By: Relevance
“…The freebase calix[6]phyrin ligands (transoid, 1 and cisoid, 2)w ere previously reported by our group, which serve as the rectangular-shaped macrocyclicl igands. [14] The two isomeric macrocycles, 1 and 2,i nw hich the arrangement of the nitrogen atomso ft he N-confused pyrrole rings (highlightedi ng reen) is different, provide two organopalladium cation pockets surroundedb ys ymmetrical and unsymmetrical coordination donor sites, "NNNC-NNNC"a nd "NNNN-NNCC", respectively.T he corresponding bis-organopalladium metal complexes, 1-Pd-Pd and 2-Pd-Pd,w ere formeds moothly using 3equivalents of Pd(OAc) 2 under reflux condition in aC H 2 Cl 2 / MeOH mixture, in 60 and 72 %y ields, respectively.A long with the formationofb is-palladium complexes, the mono-palladium complexes, 1-Pd-H 2 and 2-Pd-H 2 ,w ere also formed in 30 % and 22 %y ields, respectively.W hen one equivalent of Pd(OAc) 2 was added into the solution containing al igand 1 or 2,m onopalladium complex, 1-Pd-H 2 or 2-Pd-H 2 wasp redominantly obtained in 80 and7 5% yields, respectively.T he 1 Ha nd 19 FNMR spectroscopy and high-resolution mass spectrometry support the expected structures( cf. Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The freebase calix[6]phyrin ligands (transoid, 1 and cisoid, 2)w ere previously reported by our group, which serve as the rectangular-shaped macrocyclicl igands. [14] The two isomeric macrocycles, 1 and 2,i nw hich the arrangement of the nitrogen atomso ft he N-confused pyrrole rings (highlightedi ng reen) is different, provide two organopalladium cation pockets surroundedb ys ymmetrical and unsymmetrical coordination donor sites, "NNNC-NNNC"a nd "NNNN-NNCC", respectively.T he corresponding bis-organopalladium metal complexes, 1-Pd-Pd and 2-Pd-Pd,w ere formeds moothly using 3equivalents of Pd(OAc) 2 under reflux condition in aC H 2 Cl 2 / MeOH mixture, in 60 and 72 %y ields, respectively.A long with the formationofb is-palladium complexes, the mono-palladium complexes, 1-Pd-H 2 and 2-Pd-H 2 ,w ere also formed in 30 % and 22 %y ields, respectively.W hen one equivalent of Pd(OAc) 2 was added into the solution containing al igand 1 or 2,m onopalladium complex, 1-Pd-H 2 or 2-Pd-H 2 wasp redominantly obtained in 80 and7 5% yields, respectively.T he 1 Ha nd 19 FNMR spectroscopy and high-resolution mass spectrometry support the expected structures( cf. Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The peripheral b-protons appear in the typical sp 2 -CH region due to the non-global p-conjugation as seen in the bis-platinum calixphyrincomplexes. [14] The molecular structureso ft he complexes, 1-Pd-H 2 , 2-Pd-H 2 , 3-Pd-Pd,a nd 4-Pd-Pd,w ere characterizedb yX -ray crystallographic analysis ( Figure 2a nd S7, Table S1). The palladium cations reside in as quare planar geometry in the inner coordination environments for all the complexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The macrocycles 3a-c were prepared by condensing one equivalent of 4 with one equivalent of appropriate dipyrromethane 5 in CH 2 Cl 2 in the presence of 0.1 equivalent of TFA under a N 2 atmosphere at room temperature for 1 h followed by oxidation with DDQ in air for additional 1 h. TLC analysis showed mainly one major red spot and absorption spectroscopy showed one broad band at ∼450 nm indicating the formation of a macrocycle. 7,[13][14][15][23][24][25][26][27][28] The crude compound was subjected to alumina column chromatography and afforded the macrocycles 3a-c as orange red solids in 16-19% yields. Although we expected the formation of an expanded macrocycle containing one meso-sp 3 carbon such as compound 6 (Scheme 1), the X-ray structure of one of the macrocycles and detailed NMR studies indicated the formation of an expanded dithiacalixphyrin having two meso sp 3 carbons such as macrocycles 3a-c.…”
Section: Resultsmentioning
confidence: 99%